International Patterns of Pension Provision II : A Worldwide Overview of Facts and Figures - Pallares-Miralles, Montserrat; Romero, Carolina; Whitehouse, Edward (World Bank, Washington, DC, 2013)
This paper presents and explains cross country data for mandatory publicly and privately managed pension systems around the world. This report is organized into three parts corresponding to three broad types of indicators. These indicators relate to: (i) the relevant contextual factors referred to here as environment; (ii) pension system design parameters; and (iii) indicators of performance. Part one of the report provides some information on the environment in which the system operates, focusing on demographic and labor market conditions. Understanding the current and future path of demographic patterns, especially aging, will place the later section on performance into a clearer perspective. Part two on pension system design uses a standardized taxonomy to describe differences across countries. The data on system design are presented in two groups of indicators: (i) overall architecture of the system: pillars, schemes including civil servants and other special schemes, and (ii) operating parameters of the system, which includes two sub-groups: a) qualifying conditions: pension eligibility ages, and contribution history, and b) contribution rates, defined benefit (DB), and defined contribution (DC) schemes, and indexation. It should be noted that while many countries have more than one program providing retirement income benefits, unless otherwise indicated, most of the data refer only to the national scheme. Part three presents a set of performance indicators. The indicators included are core pension indicators that illustrate six key criteria of any pension scheme, namely: (i) coverage, (ii) adequacy, (iii) financial sustainability, (iv) economic efficiency (i.e., minimizing the distortions of the retirement?income system on individuals' behavior, such as labor supply and savings outside of pension plans), (v) administrative efficiency, and (vi)) security of benefits in the face of different risks and uncertainties.